2016
DOI: 10.1039/c6nr02614a
|View full text |Cite
|
Sign up to set email alerts
|

Graphene quantum dots conjugated with polymers for two-photon properties under two-photon excitation

Abstract: Few studies have investigated the two-photon properties of graphene quantum dots (GQDs) and GQD-conjugated polymers. The results of the present study revealed that conjugated polymers containing nitrogen and sulfur atoms caused higher quantum confinement of emissive energy to be trapped on the surface of nanomaterials, resulting in a high-photoluminescence quantum yield and notable two-photon properties. Additionally, the nanomaterials generated no reactive oxygen species-dependent oxidative stress on cells an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 24 publications
2
34
0
Order By: Relevance
“…In contrast, one-layer GO-POAA and GO-chitosan sheets are 1.5 and 1.7 nm thick, respectively, because the POAA and chitosan is successfully adsorbed on the surfaces of the GO sheets (Fig. 1 h, i) [ 11 , 15 ]. Because of the presence of exposed carboxylic acid after oxidation, the zeta potential shows the surface charge of the GO to be around − 30.9 mV.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, one-layer GO-POAA and GO-chitosan sheets are 1.5 and 1.7 nm thick, respectively, because the POAA and chitosan is successfully adsorbed on the surfaces of the GO sheets (Fig. 1 h, i) [ 11 , 15 ]. Because of the presence of exposed carboxylic acid after oxidation, the zeta potential shows the surface charge of the GO to be around − 30.9 mV.…”
Section: Resultsmentioning
confidence: 99%
“…Glutathione (γ- l -glutamyl- l -cysteinyl-glycine, GSH), which is a thiol-tripeptide, can prevent damages to cellular components due to oxidation tress. The thiol group from GSH is oxidized to a disulfide bond, which converts GSH into glutathione disulfide [ 6 , 15 , 30 ]. In vitro GSH oxidation was also used to examine the generated O 2 · − anions that are generated from GO- and GO-based materials (10–100 μg mL −1 ) for bacteria that are treated with both culture media for 3 h of incubation (Additional file 1 : Figure S3) [ 6 ] and the oxidation is summarized in Tables 6 , 7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As the latest member of the graphene family, graphene quantum dots (GQDs), which can be a promising alternative to traditional semiconductor quantum dots, show promising applications and potential developments in terms of bioimaging, electrochemical biosensors, photovoltaic devices and in the biomedical field, among many others [ 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. GQDs are generally derived from glucose, carbon fibers, graphite, graphene oxides, and synthesized or fabricated by methods like electrochemical oxidation, lithographic patterning, hydrothermal, microwave, acidic oxidation and supercritical fluid treatment [ 15 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. The high price of the carbon source (graphite, carbon fibers, and carbon nanotubes), long processing time (24–48 h), post-purification procedure (3–5 days) and the harsh reaction conditions (nitrating mixture or oxidizing supercritical water) for the large-scale production of GQDs are uneconomic and unreasonable, so it is imperative and desirable to prepare GQDs in a more facile, milder and more environmentally-friendly method [ 18 , 19 , 21 , 23 , 24 , 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…1d, the D band at ≈ 1360 cm −1 and G band at ≈ 1600 cm −1 could also be observed, which are attributed to the sp 2 graphitized structure and local defects/disorders of carbonaceous materials, respectively. The high ratio of D/G peak intensity demonstrated that large amounts of defects and disorders existed in the edge or surface of the GQDs structure [31].
Fig.
…”
Section: Resultsmentioning
confidence: 99%